Molecular Detection of Stx1 and Stx2 Genes in E. coli O 157:H7 Isolated from Soft White Cheese - Yassin, Safana A.S. (Iraqi Journal of Science, 2025)
Foodborne diseases are increasingly reported to be caused by Escherichia coli O157:H7. Therefore, the current study was conducted to determine the incidence of this bacterium in locally produced soft white cheese. A total of 36 samples were collected from local markets in different places of Baghdad city. The process of bacterial isolation was performed by culturing onto different media, such as MacConkey Agar, Eosin Methylene Blue Agar and Sorbitol MacConkey Agar (SMAC). The identification of bacteria was achieved by biochemical tests and confirmed by a molecular technique. Multiplex polymerase chain reaction (m-PCR) was used through the detection of rfb O157 and flic H7 genes. Some genes of virulence factors, such as Shiga-toxin genes (Stx1and Stx2), were also investigated by PCR.  In this study, the results showed that the total number of E. coli isolates was 6/36 (16.7%) and only 1/36(2.8%) of the isolates were of the E. coli O157:H7 strain. The identified isolate of E. coli O157:H7 was positive for the Stx2 gene; 1/6 (16.7%) of  E.coli isolates, while it was negative for Stx1; 0/6 (0%). In terms of occurrence, this bacterium was less found than those reported by previous researches in Iraq. This study demonstrated that soft white cheese made locally in Baghdad City has a significant probability of containing the Shiga-Toxin E. Coli (STEC).